Exacerbation of Congenital Hydronephrosis as the First Presentation of COVID-19 Infection in Children - Masoumeh Mohkam; Mahnaz Jamee; Farshid Kompani; Mitra Khalili; Atena Seifi; Leily Mohajerzadeh (Case Reports in Nephrology)
Background. Congenital hydronephrosis is one of the most common abnormalities of the upper urinary tract, which can be exacerbated by a variety of intrinsic or extrinsic triggers. The urinary tract system is one of the major organs complicated by COVID-19 infection. Case Presentations. Here, we report five patients with an established diagnosis of congenital hydronephrosis, who presented with acute abdominal pain and fever and an abrupt increase in the anteroposterior pelvic diameter (APD). Patients had a previous stable course and were under regular follow-up with serial ultrasonographic studies. They underwent surgery or supportive treatment due to the later exacerbation of hydronephrosis. Based on the clinical and imaging findings, no plausible etiologies for these exacerbation episodes, including infection, nephrolithiasis, or abdominal masses, could be postulated. The common aspect in all these patients was the evidence of a COVID-19 infection. Conclusions. Infection with COVID-19 in children with antenatal hydronephrosis may exacerbate the degree of hydronephrosis and renal APD in ultrasonography, which itself may be mediated by the increase in inflammatory mediators.